THE POLITICAL ECONOMY OF â€œNEW NORMALâ€ POLICY TOWARD GREEN ECONOMY AGENDA IN CHINA - Wilda Fatma Apsari (HI 16 UMY 060, 2016)
*60 Excellent growth of China in export-led business created this state into a giant state not only in width of region or number of population but in economy and politics as well. However, with this kind of development China also having so many problem within the country. This research elaborates the policy of China that decreasing its economic target from 10 percent to 7 percent in the middle of its great development in perspective of rational choice on decision making process and the concept of economic diplomacy. An interesting topic to discuss that China decided this policy in reason of increasing its existence in international world order beside to embody the green development for sustaining its domestic development. The shifting of leadership in 2013 is brought China into greener development policy oriented. China is trying to drive the slower but high-quality development and projects become more cooperative with its neighboring country and beyond. Keywords: New Normal, Chinese Dream, Green Development, Economic Diplomacy, Rational Choices